Submarine Cable
By employing a specific polymer combination in the insulating layer of submarine cable cores, the challenges of water tree degradation and high dielectric loss in wet design submarine power cables are addressed, resulting in improved electrical breakdown strength and reduced dielectric losses in saltwater environments.
Patent Information
- Application Number
- JP2024560423
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-12
- Filing Date
- 2023-04-12
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-04-12
AI Technical Summary
Wet design submarine power cables face challenges in balancing salt water wet aging performance with dielectric loss, particularly at high voltages, due to water tree degradation and increased dielectric loss in polymer WTR solutions.
The use of an insulating layer in submarine cable cores comprising a combination of LDPE homopolymer or copolymer with polyunsaturated comonomers and a copolymer with low amounts of polar monomer units, balanced to achieve optimal brine wet aging performance and low dielectric loss.
This solution effectively enhances the electrical breakdown strength in saltwater environments while maintaining low dielectric losses, thus improving the reliability and efficiency of submarine power cables.
Smart Images

Figure 2025512056000001 
Figure 2025512056000002 
Figure 2025512056000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a wet design cable for saltwater environments (hereinafter referred to as submarine cable), in particular to a wet design submarine power cable operating at high voltage, i.e. a submarine power cable, comprising at least one cable core provided with an insulating layer with effective water tree retardation using a blend of polyolefin and polar copolymer, in particular a blend of LDPE and polar copolymer. The present invention further relates to a method for preparing such a submarine cable and to the use of such a submarine cable in a seawater environment, e.g. in a submarine environment. [Background technology]
[0002] Sustainable development, defined as "development that meets the needs of the present without compromising the ability of future generations to meet their own needs," is a central theme worldwide, and the cable industry, as a technology supplier to the power industry, is supporting many of the changes the industry is making to achieve a more sustainable power system.
[0003] Power cables can play a major role in sustainable development, for example by enabling the integration of offshore renewable energy sources in remote locations through submarine power cable technology. Submarine cables are employed in several scenarios, for example in wind farms or wave and tidal power systems, supplying offshore renewable energy to land, powering islands, connecting autonomous power grids, powering marine platforms, short-haul crossing (e.g., transporting electricity across rivers, waterways, straits, fjords, bays or lakes). Typically, these submarine cable systems transport electricity at high voltage (HV).
[0004] From a sustainable development perspective, it is also important that materials used for power cables, including submarine power cables, are designed with sustainable performance in mind, and to focus on the possibility of facilitating the handling of cables at the end of their life (EOL) in order to contribute to a circular economy.
[0005] A typical power cable comprises at least one cable core, each comprising a conductor surrounded, in order, by an inner semiconductive layer (also called a conductor shield), an insulating layer, and an outer semiconductive layer (also called an insulation shield). The cable may comprise additional components and layers, such as a jacketing layer, as is well known in the art.
[0006] To protect cables from problems caused by moisture ingress when the cables are used underwater, it is known to cover the cables with a moisture impervious layer, typically a metallic moisture impervious layer. This is called dry cable design. The moisture impervious layer prevents water ingress into the cable, but it significantly increases the raw material cost of the cable and is expensive to apply. Also, conventional moisture impervious layers are often made of lead, which has a large impact on the environment.
[0007] In comparison to the dry design, there is the so-called wet design or wet cable construction, which is defined as a cable construction in which there is no moisture-tight layer. Such a design therefore lacks a moisture-tight layer, in particular an extruded metallic moisture-tight layer. The terms "dry" and "wet" are well known in the art and are explained in Cigre TB722.
[0008] A wet design cable construction allows for the migration of water or moisture into the interior of the cable core. This allows for the use of a "simpler" cable design in which at least one layer and its corresponding manufacturing steps are omitted, thus reducing material consumption and improving the sustainability performance of the cable design. At the same time, the elimination of the moisture impermeable layer (often an extruded metal sheet) makes the cable easier to handle at the end of its life, thus improving its sustainability performance.
[0009] However, it is known that water does not easily penetrate into the interior of a power cable, and the service life of the insulated cable is often shortened when the polymer insulation is installed in an environment where it is exposed to water, such as underground, in a place with high humidity, or underwater.
[0010] The combination of electric fields and water can cause water tree degradation of insulating materials, which is influenced by the presence of inhomogeneities, microvoids and impurities in the insulating material. Water tree formation results in localized damage of the insulation, leading to reduced electrical breakdown strength. Water tree growth can ultimately result in electrical breakdown or electrical failure.
[0011] Therefore, in the wet design cables, care must be taken to maximize the water tree retardant (WTR) in the cable insulation, and these cables must be subjected to rigorous testing, such as wet ageing tests, to demonstrate that they exhibit sufficient water resistance.
[0012] One proven WTR technology is the so-called "polymer WTR", where a polar copolymer is added to an LDPE type matrix. WTR solutions are well known in the art and have been described in various literature disclosures.
[0013] In European Patent Application EP 1 731 566, the combination of an unsaturated polyolefin having a particular vinyl content with a polar copolymer is taught to improve humid aging properties.
[0014] WO 2010 / 112333 describes a cable comprising a conductor surrounded by a semiconductive layer and an insulating layer, the semiconductive layer consisting of a composition (A) consisting of a polar copolymer (a) and carbon black, the insulating layer consisting of a composition (B) comprising a polar copolymer, the difference between the melting temperature Tm(b2) of the polar copolymer (a) and the melting temperature Tm(b2) of the polar copolymer (b2) being less than 25°C.
[0015] International Publication No. WO 85 / 05216 describes an insulation composition consisting of polyethylene and 10-40% by weight of a (meth)acrylate polymer, such as EBA.
[0016] JP 08-319381 A illustrates several blends based on EMA and LDPE and test sheets which are subjected to a water tree test in very strong saline solution (2 mol / L).
[0017] Because submarine power cables are exposed to very harsh conditions (e.g., seawater is potentially corrosive) and typically operate at high voltages (RMS value of the voltage between any two conductors or phases in a three-phase cable) of 33 kV, 66 kV, and above 66 kV, the inventors are particularly interested in the wet aging performance of submarine power cables in salt water environments (as described in Cigre TB722) operating at these high voltages.
[0018] Designing submarine cables exposed to salt water is difficult because salt water or sea water also tends to exacerbate the problem of water treeing in the cable, as observed in small-scale tests. Salt water can contain not only sodium chloride but also magnesium, calcium, potassium and sulfate ions, etc. These dissolved salts can affect water tree formation in wet-design cables. Salt water, e.g., sea water, is a more aggressive environment than, e.g., fresh water. Thus, materials that can function in a fresh water environment may not be able to withstand exposure to sea water.
[0019] Moreover, as mentioned above, submarine power cables typically operate at high voltages. This places demands on the level of dielectric losses in the selected insulating material. The dielectric losses are linearly proportional to tan δ and are preferably kept as low as possible for technical and economic reasons, but also from a sustainability point of view. Lower losses mean that less of the transmitted electrical energy is lost as heat energy in the cable core insulation. These losses represent economic losses for the power line operator. Lower losses also reduce the risk of thermal runaway, i.e. an unstable situation in which the temperature of the insulation increases due to tan δ. If the temperature increases, tan δ usually also increases. This further increases the dielectric losses and therefore the temperature. The result would be a dielectric failure of the cable. Summary of the Invention [Problem to be solved by the invention]
[0020] As mentioned above, wet design cables often use WTR solutions, such as polymeric WTR, to provide sufficient water resistance, but a drawback of the polymeric WTR solutions is that the dielectric loss, as measured by tan δ, can be increased compared to the dielectric loss in dry design polymer solutions typically used for high voltage (HV) applications.
[0021] Therefore, there is a need to identify a submarine cable core material system (i.e., a combination of materials for one or more insulating layers and materials for the semiconducting layers of a submarine cable core) that can be used in seawater environments at high pressure and that balances salt water wet aging performance as well as the level of dielectric loss as measured by tan δ, while maintaining good sustainability performance.
[0022] A wet design cable is presented in Johansson et al 8th International Conference on Insulated Power Cables, Influence of submarine conditions on the long-term performance of AC XLPE cables, Jicable'11-19-23 June 2011, Versailles-France. The cables tested use a high performance water tree flame retardant copolymer XLPE.
[0023] In Jicable'19, Paris 23-27 June 2019, Featherstone et al. "Full scale wet age testing of XLPE insulated power cables in salt water" saline testing of wet-design XLPE cables was reported. [Means for solving the problem]
[0024] The present invention is based on the surprising discovery that the above-mentioned needs can be met by an insulating layer for wet-design submarine cables and cable cores, in particular wet-design submarine power cables and cable cores, which insulating layer comprises a combination of (i) an LDPE homopolymer or LDPE copolymer having a polyunsaturated comonomer and (ii) a copolymer containing a low amount of polar monomer units, for example in the composition in which the amount of polar monomer units in the total polymer fraction is between 1 and 150 micromoles (1×10) per gram. -6 ~150×10 -6 mol) and offers a good balance between salt water wet aging performance and dielectric loss as measured by tan δ.
[0025] The particular polymer combinations in the insulating and semiconducting layers defined herein are novel in their ability to withstand dielectric breakdown in salt water environments while maintaining acceptable dielectric loss or tan δ.
[0026] Viewed from one aspect, the present invention provides a submarine cable core, e.g. for transmitting electrical power, in a saltwater environment, e.g. under the sea or on the seabed, comprising: the cable core comprises a conductor surrounded by at least an inner semiconducting layer, an insulating layer, and an outer semiconducting layer, in that order; The insulating layer is (i) a low density polyethylene homopolymer or copolymer comprising at least one polyunsaturated comonomer and, optionally, one or more further comonomers; and (ii) a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, and vinyl acetates; Including, wherein the amount of polar monomer units in the insulating layer is 1 to 150 micromoles per gram based on the total amount of polymer in the insulating layer; The above submarine cable core is provided.
[0027] Viewed from another aspect, the present invention provides a submarine cable core, for example for transmitting electricity, in a saltwater environment, for example under the sea or on the seabed, comprising: the cable core comprises a conductor surrounded by at least an inner semiconducting layer, an insulating layer, and an outer semiconducting layer, in that order; The insulating layer is (i) a low density polyethylene homopolymer or copolymer comprising at least one polyunsaturated comonomer and, optionally, one or more further comonomers; and (ii) a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, and vinyl acetates; Including, wherein the amount of polar monomer units in the insulating layer is 1 to 150 micromoles per gram based on the total amount of polymer in the insulating layer; and wherein the inner semiconductor layer and the outer semiconductor layer independently comprise: (a) a low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, or vinyl acetates; and (b) Carbon black Including, The above submarine cable core is provided.
[0028] Viewed from yet another aspect, the present invention provides a method of using a submarine cable core comprising a conductor surrounded, in order, by at least an inner semiconducting layer, an insulating layer, and an outer semiconducting layer, the method comprising the steps of: The insulating layer is (i) a low density polyethylene homopolymer or copolymer comprising at least one polyunsaturated comonomer and, optionally, one or more further comonomers; and (ii) a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, and vinyl acetates; Including, wherein the amount of polar monomer units in the insulating layer is 1 to 150 micromoles per gram based on the total amount of polymer in the insulating layer; and wherein the inner semiconductor layer and / or the outer semiconductor layer independently comprise: (a) a low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, or vinyl acetates; and (b) Carbon black Including, The above method is provided.
[0029] Viewed from one aspect, the present invention provides a submarine cable comprising at least one submarine cable core as defined above, preferably at least three submarine cable cores.
[0030] The submarine cable of the present invention is preferably a submarine cable of wet design.
[0031] The submarine cable core of the present invention is crosslinkable or crosslinked. Thus, in a further embodiment, the insulating layer further comprises a crosslinking agent, preferably a peroxide, and is crosslinkable. In a further embodiment, the inner semiconducting layer and / or the outer semiconducting layer further comprises a crosslinking agent, preferably a peroxide, and is crosslinkable. In a further embodiment, the insulating layer, the inner semiconducting layer and the outer semiconducting layer further comprise a crosslinking agent, preferably a peroxide, and are crosslinkable. When subjected to crosslinking conditions, the crosslinkable submarine cable core can be crosslinked. The peroxide decomposes and generates free radicals that initiate the crosslinking reaction in the composition. Thus, after the crosslinking reaction, the peroxide is essentially completely consumed.
[0032] Viewed from another aspect, the present invention provides a crosslinked submarine cable core obtainable by crosslinking a crosslinkable submarine cable core as defined herein above.Viewed from another aspect, the present invention provides a method of using a crosslinked submarine cable core as defined herein above in a submarine cable, for example in a submarine cable for carrying power, in a salt water environment, for example under the sea or on the sea bed.
[0033] Viewed from another aspect, the present invention is a method for manufacturing a submarine cable core having a conductor surrounded, in order, by at least an inner semiconducting layer, an insulating layer, and an outer semiconducting layer, the method comprising: extruding, e.g., coextruding, an inner semiconducting layer, an insulating layer, and an outer semiconducting layer onto the conductor; and Crosslinking one or more of the inner semiconducting layer, the insulating layer, and the outer semiconducting layer. The process includes the steps of: Here, the insulating layer is (i) a low density polyethylene homopolymer or copolymer comprising at least one polyunsaturated comonomer and, optionally, one or more further comonomers; and (ii) a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, and vinyl acetates; Including, wherein the amount of polar monomer units in the insulating layer is 1 to 150 micromoles per gram based on the total amount of polymer in the insulating layer; and wherein the inner semiconductor layer and the outer semiconductor layer independently comprise: (a) a low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of an alkyl acrylate, an alkyl methacrylate, or vinyl acetate; and (b) Carbon black Includes The above method is provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0034] The present invention provides a submarine cable core for use in a saltwater environment and a submarine cable comprising the submarine cable core, for example a crosslinkable or crosslinked submarine cable, for example a crosslinkable or crosslinked submarine power cable, the submarine cable core comprising at least one cable core comprising a conductor surrounded by at least an inner semiconducting layer, an insulating layer and an outer semiconducting layer. The present invention also relates to a crosslinkable submarine cable comprising a conductor surrounded by at least an inner semiconducting layer, an insulating layer and an outer semiconducting layer.
[0035] As used herein in the specification and claims, the term "salt water" or "salt water environment" refers to water containing dissolved sodium chloride (NaCl) having a NaCl content of 1.0% by weight or more, preferably 2.0% by weight or more, more preferably 3.0% by weight or more, or up to 10% by weight or less, preferably 8% by weight or less, more preferably 6% by weight or less, based on the total weight of the water.
[0036] As used herein, the term "cable" is intended to denote a cable comprising at least one cable core, optionally two cable cores, preferably three cable cores. As used herein, each "cable core" comprises a conductor surrounded by at least an inner semiconducting layer, an insulating layer, and an outer semiconducting layer.
[0037] One or more cable cores in the cable may be surrounded by at least one reinforcing and / or armoring layer adapted for mechanical protection of the cable. The armoring layer may include metal wires, braid, sheath, or low loss armor. These variations and cable constructions are well known to those skilled in the art. The armoring layer may extend across a portion of the cable.
[0038] The term "AC cable" refers to an alternating current (AC) cable having at least three cable cores, one for each of the three phases.
[0039] The term "submarine," as defined above, is intended to denote at least partially beneath or in salt water (e.g., salt lakes, seas, oceans, etc.). For example, a submarine cable is a cable that runs at least partially beneath or through salt water.
[0040] Throughout this specification the term "high voltage" or HV refers to voltages above 33 kV, preferably above 36 kV (the RMS value of the voltage between any two conductors or phases in a three-phase cable).
[0041] The submarine cable comprising at least one cable core of the present invention is preferably of wet design as defined herein above. Ideally, the submarine cable does not comprise a moisture impervious layer that prevents the ingress of water. Despite its wet design, the submarine cable comprising at least one cable core of the present invention provides excellent resistance to water treeing in salt water environment while maintaining acceptable dielectric loss performance. This can be demonstrated through analysis of electrical breakdown strength after wet aging of the cable core in salt water and through tan δ measurement, respectively. Thus, from another point of view, the present invention provides a submarine cable core, and thus a submarine cable, with improved electrical breakdown strength in salt water environment while maintaining low dielectric losses.
[0042] Some experts consider the presence of a polymeric jacket over the outer semiconducting layer to be a "semi-wet" design because the jacket layer limits the rate of water vapor infiltration. The inventors consider such a solution herein a wet design because the jacket layer is impermeable to water or moisture.
[0043] Insulation layer
[0044] The submarine cable core of the present invention comprises: (i) a low density polyethylene homopolymer or copolymer comprising at least one polyunsaturated comonomer and, optionally, one or more further comonomers; and (ii) a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, and vinyl acetates; and an insulating layer comprising: Here, the amount of the polar monomer unit in the insulating layer is 1 to 150 micromoles per gram based on the total amount of polymer components in the insulating layer.
[0045] Low density polyethylene homopolymer or copolymer with at least one polyunsaturated comonomer and optionally one or more further comonomers - Insulating layer
[0046] Component (i) of the insulating layer is an LDPE homopolymer or copolymer having at least one polyunsaturated comonomer and optionally one or more further comonomers, referred to herein as LDPE polymer component (i).
[0047] The term "LDPE" is an abbreviation for low density polyethylene, but the term is not intended to limit the range of densities and is understood to include LDPE-like high pressure polymerized (HP) polyethylene. The term "LDPE" describes and distinguishes only the properties of HP polyethylene, which has typical characteristics, such as different branching structure, compared to polyethylene produced in the presence of olefin polymerization catalysts.
[0048] The term "LDPE homopolymer" will generally be understood to refer to a low density polyethylene polymer consisting essentially of ethylene monomer. Ideally, therefore, LDPE homopolymers contain no comonomers. However, small amounts of comonomers other than ethylene that do not significantly affect the properties of LDPE may be tolerated since such materials are still essentially homopolymers. In this regard, a small amount of comonomer may be understood to be less than 3% by weight, e.g., less than 1% by weight, less than 0.5% by weight, or less than 0.1% by weight, of comonomers other than ethylene, based on the total weight of the LDPE homopolymer.
[0049] It is preferred that the LDPE polymer component (i) is an LDPE copolymer having at least one polyunsaturated comonomer.
[0050] In one embodiment, the LDPE polymer component (i) is an LDPE copolymer having at least one polyunsaturated comonomer and optionally one or more further comonomers.
[0051] Preferably, the LDPE copolymer component (i) is a binary copolymer of ethylene and only one polyunsaturated comonomer.
[0052] The polyunsaturated comonomer preferably comprises a linear carbon chain having at least 8 carbon atoms and at least 4 carbon atoms between non-conjugated double bonds, at least one of which is terminal. The polyunsaturated comonomer is preferably a diene, for example a diene having at least 8 carbon atoms, a first carbon-carbon double bond being terminal and a second carbon-carbon double bond being non-conjugated to the first carbon-carbon double bond, for example a C8-C 14non-conjugated dienes or combinations thereof, such as 1,7-octadiene, 1,9-decadiene, 1,11-dodecadiene, 1,13-tetradecadiene or combinations thereof, such as 1,7-octadiene, 1,9-decadiene, 1,11-dodecadiene and 1,13-tetradecadiene.
[0053] If another comonomer is present, this is C3-C 10 It may be an alpha-olefin.
[0054] The LDPE copolymer component (i) preferably comprises in total 0.001 to 40% by weight, preferably 0.05 to 40% by weight, more preferably 0.05 to 30% by weight, even more preferably 0.10 to 30% by weight, even more preferably 0.10 to 20% by weight of one or more comonomers (i.e. all comonomers), based on the total weight of the LDPE copolymer. In one embodiment, the LDPE copolymer comprises in total 0.05 to 20% by weight, preferably 0.05 to 15% by weight, for example 1.0 to 10% by weight, in particular 0.05 to 5.0% by weight, for example 1.0 to 5.0% by weight, more in particular 0.05 to 3.0% by weight, for example 0.10 to 3.0% by weight of comonomers.
[0055] The polyunsaturated comonomer content is preferably 0.001 to 10% by weight, more preferably 0.01 to 10% by weight, even more preferably 0.01 to 5.0% by weight, even more preferably 0.01 to 3.0% by weight, in particular 0.01 to 2.0% by weight, more in particular 0.1 to 2.0% by weight. In some embodiments, the only comonomer present is a polyunsaturated comonomer. The polyunsaturated comonomer content is preferably 0.001 to 10% by weight, preferably 0.01 to 10% by weight, more preferably 0.01 to 5.0% by weight, even more preferably 0.01 to 3.0% by weight, in particular 0.01 to 2.0% by weight, more in particular 0.1 to 2.0% by weight. In some embodiments, the only comonomer present is a polyunsaturated comonomer.
[0056] The LDPE polymer component (i) is preferably unsaturated. The LDPE polymer component (i) preferably has a total amount of carbon-carbon double bonds of more than 0.4 / 1000 carbon atoms, preferably more than 0.5 / 1000 carbon atoms, such as more than 0.6 / 1000 carbon atoms, particularly more than 0.7 / 1000 carbon atoms, such as more than 0.8 / 1000 carbon atoms. The upper limit of the amount of carbon-carbon double bonds present in the polyolefin is not particularly limited, and can be preferably less than 5.0 / 1000 carbon atoms, more preferably less than 3.0 / 1000 carbon atoms.
[0057] In some embodiments, the total amount of carbon-carbon double bonds derived from vinyl, vinylidene and trans-vinylene groups, if present in the LDPE polymer component (i), is greater than 0.40 / 1000 carbon atoms, preferably greater than 0.50 / 1000 carbon atoms, more preferably greater than 0.60 / 1000 carbon atoms, even more preferably greater than 0.70 / 1000 carbon atoms, still more preferably greater than 0.75 / 1000 carbon atoms, especially greater than 0.8 / 1000 carbon atoms. Preferably, the total amount of carbon-carbon double bonds derived from vinyl, vinylidene and trans-vinylene groups is less than 5.0 / 1000 carbon atoms, preferably less than 3.0 / 1000 carbon atoms.
[0058] In some embodiments, the LDPE polymer component (i) comprises at least vinyl groups, and the total amount of vinyl groups is preferably more than 0.05 / 1000 carbon atoms, even more preferably more than 0.08 / 1000 carbon atoms, and most preferably more than 0.11 / 1000 carbon atoms. In some embodiments, the LDPE polymer component (i) comprises at least vinyl groups, and the total amount of vinyl groups is preferably more than 0.10 / 1000 carbon atoms, such as more than 0.15 / 1000 carbon atoms, such as more than 0.20 / 1000 carbon atoms, more preferably more than 0.25 / 1000 carbon atoms, particularly more than 0.30 / 1000 carbon atoms, more particularly more than 0.35 / 1000 carbon atoms, and most particularly more than 0.40 / 1000 carbon atoms, such as more than 0.45 / 1000 carbon atoms or more than 0.50 / 1000 carbon atoms.
[0059] Preferably, the total amount of vinyl groups is less than 4.0 / 1000 carbon atoms. More preferably, the LDPE polymer component (i) before crosslinking contains a total amount of vinyl groups greater than 0.20 / 1000 carbon atoms, even more preferably greater than 0.30 / 1000 carbon atoms, most preferably greater than 0.40 vinyl / 1000 carbon atoms, such as greater than 0.45 vinyl / 1000 C(carbon atoms).
[0060] It is understood that, herein, all amounts or values relating to unsaturation in general, such as vinyl, vinylidene and trans-vinylene groups, refer to the amounts or values determined prior to crosslinking.
[0061] Preferably, the LDPE polymer component (i) has a melt flow rate MFR2.16 / 190°C of 0.1 to 50 g / 10 min, preferably 0.3 to 20 g / 10 min, more preferably 0.3 to 15 g / 10 min, even more preferably 0.50 to 15 g / 10 min, or 0.60 to 10 g / 10 min, for example 0.60 to 3.0 g / 10 min. In some embodiments, MFR2 is 0.50 to 8.0 g / 10 min, for example, 0.60 to 6.0 g / 10 min, preferably 0.70 to 5.5 g / 10 min, for example, 0.80 to 5.0 g / 10 min, more preferably 0.90 to 4.75 g / 10 min, even more preferably 1.0 to 4.5 g / 10 min, still even more preferably 1.1 to 4.25 g / 10 min, and most preferably 1.2 to 4.0 g / 10 min, for example, 1.2 to 3.0 g / 10 min.
[0062] The optional LDPE polymer component (i) has a viscosity of 905 to 935 kg / m 3 , preferably 910 to 935 kg / m 3 , for example 910~928kg / m 3 , may have a density of
[0063] The insulating layer is preferably free of carbon black.
[0064] The insulating layer may comprise at least 90% by weight of the LDPE polymer component (i), for example at least 91%, at least 92%, at least 93%, at least 94%, in particular at least 95% or at least 96%, and up to 99.5% by weight, in particular up to 99% by weight, based on the total weight of the insulating layer. It is possible to use a blend of LDPE polymers as component (i). When a blend of LDPE polymers is used, this percentage refers to the total of the LDPE polymers present.
[0065] The LDPE polymer component (i) generally forms the balance of the layer when the other components are taken into account.
[0066] Polar copolymer - A copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetates - Insulating layer
[0067] The insulating layer also comprises a copolymer (also named component (ii) or polar copolymer) comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates or vinyl acetates. It is possible to use mixtures of such components (ii).
[0068] The copolymer comprising at least one polar comonomer is preferably a low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate as a polymer water tree retarder. This copolymer can be the same as or different from the low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate used in the inner and outer semiconducting layers. In general, the definition of low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate provided below applies to component (ii) of the insulating layer as well as to component (a) of the inner and outer semiconducting layers.
[0069] The one or more polar comonomers of the low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate are preferably selected from C1- to C6-alkyl acrylates, C1- to C6-alkyl methacrylates or vinyl acetate. Even more preferably, the LDPE copolymer used is a copolymer of ethylene and C1- to C6-alkyl acrylates, such as methyl, ethyl acrylate, propyl acrylate or butyl acrylate or vinyl acetate.
[0070] Preference is given to using ethylene methyl acrylate (EMA) copolymers, ethylene methyl methacrylate (EMMA) copolymers, ethylene ethyl acrylate (EEA) copolymers, ethylene ethyl methacrylate (EEMA) copolymers, ethylene butyl methacrylate (EBMA) copolymers, ethylene butyl acrylate (EBA) copolymers or ethylene vinyl acetate (EVA) copolymers.
[0071] Particular preference is given to using ethylene methyl acrylate (EMA), ethylene butyl acrylate (EBA) or ethylene ethyl acrylate (EEA).
[0072] The copolymer comprising at least one polar comonomer of the insulating layer preferably comprises 0.001 to 40% by weight, more preferably 0.05 to 40% by weight, even more preferably 1 to 30% by weight of one or more comonomers, based on the total weight of the copolymer. The polar comonomer content is more preferably 5 to 30% by weight, 5 to 25% by weight, 5 to 20% by weight, for example 7 to 25% by weight, in particular 7 to 20% by weight, 10 to 25% by weight or 10 to 30% by weight.
[0073] Preferably, the copolymer containing at least one polar comonomer of the insulating layer has a melt flow rate MFR2.16 / 190°C of 0.1 to 50 g / 10 min, more preferably 1.0 to 30 g / 10 min, even more preferably 2.0 to 25 g / 10 min, and most preferably 2.0 to 22 g / 10 min. In some embodiments, the copolymer containing at least one polar comonomer of the insulating layer has a melt flow rate MFR2.16 / 190°C of 0.1 to 20 g / 10 min, more preferably 0.5 to 12 g / 10 min. In an even more preferred option, the copolymer comprising at least one polar comonomer of the insulating layer has a MFR2.16 / 190°C of 2.0 to 20.0 g / 10 min, such as 2.0 to 17.0 g / 10 min, preferably 2.0 to 15.0 g / 10 min, such as 2.0 to 13.5 g / 10 min, 2.0 to 13.0 g / 10 min, 2.5 to 12.5 g / 10 min or 2.5 to 12.0 g / 10 min, such as 5.0 to 12.0 g / 10 min.
[0074] Copolymers containing at least one polar comonomer have a viscosity of 910 to 940 kg / m 3 , preferably 915 to 940 kg / m 3 , for example 920~940kg / m 3 , may have a density of
[0075] According to one embodiment, the insulation layer used in the cable core of the present invention comprises at least 0.5 wt.-%, preferably at least 0.60 wt.-%, such as at least 0.70 wt.-% or 0.75 wt.-%, more preferably at least 0.80 wt.-%, such as at least 0.90 wt.-%, at least 0.95 wt.-% or at least 1.0 wt.-%, of a copolymer comprising at least one polar comonomer, i.e. component (ii), relative to the total weight of the insulation layer.
[0076] In an advantageous embodiment of the invention, the insulation layer used in the cable core of the invention comprises not more than 9.0% by weight, such as not more than 8.0% by weight, preferably not more than 7.0% by weight, such as not more than 6.0% by weight, not more than 5.0% by weight, not more than 4.0% by weight or not more than 3.0% by weight, of a copolymer comprising at least one polar comonomer, i.e. component (ii), relative to the total weight of the insulation layer. When a blend of these polymers is used in component (ii), this percentage refers to the sum of the copolymers comprising at least one polar comonomer present.
[0077] In a particularly preferred embodiment of the present invention, the insulation layer used in the cable core of the present invention comprises, based on the total weight of the insulation layer, 0.5% to 9.0% by weight of a copolymer comprising at least one polar comonomer, i.e. component (ii), preferably 0.75% to 7.0% by weight, for example 0.80% to 5.0% by weight, more preferably 0.90% to 4.0% by weight, even more preferably 1.0% to 3% by weight.
[0078] Preferably, the amount of polar monomer units in the insulating layer is 1 micromol or more, such as 2.5 micromol or more, more preferably 5 micromol or more, such as 7.5 micromol or more, and even more preferably 10 micromol or more, such as 15 micromol or more or 20 micromol or more, per gram of the total amount of polymer components in the insulating layer.
[0079] Preferably, the amount of polar monomer units in the insulating layer is 150 micromoles or less, preferably 140 micromoles or less, such as 130 micromoles or less, 120 micromoles or less, more preferably 100 micromoles or less, even more preferably 80 micromoles or less, such as 75 micromoles or less, even more preferably 70 micromoles or less, such as 60 micromoles or less, even more preferably 50 micromoles or less, such as 40 micromoles or less, per gram of the total amount of polymer components in the insulating layer.
[0080] The amount of polar monomer units is expressed in micromoles per gram of the total polymer, i.e., the total polymer components, contained in the insulating layer.Of course, in the insulating layer, the polar monomer units are preferably essentially completely incorporated into the backbone of component (ii), i.e., the copolymer containing at least one polar comonomer.Following this, the LDPE homopolymer or LDPE copolymer with at least one polyunsaturated comonomer of component (i) in the insulating layer is preferably essentially free of polar monomer units.
[0081] The inventors have found that a copolymer containing at least one polar comonomer acts as a polymeric WTR and thus provides salt water wet aging performance of the insulation layer. Surprisingly, even a small amount of this polar copolymer blended with component (i) in the insulation layer provides sufficient salt water wet aging performance. Without being bound by this theory, the inventors believe that on the one hand, it is a combination of a specific "delivery mechanism" of the polar comonomer to the insulation layer (i.e., blending a polar copolymer or component (ii) into component (i) as opposed to copolymerizing a polar comonomer). The inventors believe that component (ii) forms localised "islands" of polar copolymer in the LDPE phase of component (i) in the cable core insulation. The aforementioned islands containing highly polar material of component (ii) are believed to oppose water tree growth and thus improve salt water wet aging performance, but have limited impact on dielectric loss performance. On the other hand, the particular selection of the total amount of polar comonomer in the insulating layer results in a balance between salt water wet ageing performance and dielectric loss, measured by tan δ, that is ideally suited for submarine cables, in particular submarine power cables operating at high voltages, in particular submarine AC power cables operating at high voltages.
[0082] Crosslinker - Insulating layer
[0083] The insulation layer may be crosslinkable or crosslinked. In such crosslinkable embodiments, it is preferred if the crosslinkable insulation layer comprises a peroxide. It is preferred if the crosslinkable insulation layer comprises a crosslinking agent, preferably a peroxide, after the cable core structure is formed. A mixture of peroxides may be used.
[0084] Preferred crosslinking agent is organic peroxide.Non-limiting examples are organic peroxides such as di-tert-amyl peroxide, 2,5-di(tert-butylperoxy)-2,5-dimethyl-3-hexyne, 2,5-di(tert-butylperoxy)-2,5-dimethylhexane, tert-butylcumyl peroxide, di(tert-butyl)peroxide, dicumyl peroxide, butyl-4,4-bis(tert-butylperoxy)-valerate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-butylperoxybenzoate, dibenzoyl peroxide, bis(tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 1,1-di(tert-butylperoxy)cyclohexane, 1,1-di(tert-amylperoxy)cyclohexane, or any combination thereof. Preferably, the peroxide is selected from 2,5-di(tert-butylperoxy)-2,5-dimethylhexane, di(tert-butylperoxyisopropyl)benzene, dicumyl peroxide, tert-butylcumyl peroxide, or a combination thereof. Most preferably, the peroxide is dicumyl peroxide.
[0085] The peroxide is preferably present in the insulating layer in an amount of less than 3.0% by weight, preferably 0.1 to 2.5% by weight, more preferably 0.2 to 2.5% by weight, even more preferably 0.3 to 2.25% by weight, for example 0.3 to 2.0% by weight, based on the weight of the insulating layer. When a blend of the crosslinking agents is used, this percentage refers to the total of the crosslinking agents present.
[0086] The inner semiconductor layer and the outer semiconductor layer
[0087] The inner and outer semiconducting layers can be the same or different, preferably the same. By identical in this context, it is meant that the chemical composition of the inner and outer semiconducting layers before crosslinking is the same. The inner and outer semiconducting layers are different from the insulating layer.
[0088] The semiconducting properties of the semiconducting layer are due to the conducting component contained within the semiconducting layer, namely carbon black.
[0089] It is preferred when both the inner and outer semiconducting layers comprise an LDPE copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, or vinyl acetates; and carbon black. It is preferred when both the inner and outer semiconducting layers comprise an LDPE copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, or vinyl acetates; carbon black; a peroxide; and, optionally, an antioxidant. The following discussion may be applicable to either or both of these semiconducting layers.
[0090] A low density polyethylene (LDPE) copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, and vinyl acetates - a semiconducting layer
[0091] The LDPE copolymer of the inner and / or outer semiconducting layers comprises one or more polar comonomers selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetates, or combinations thereof. It is also possible to use mixtures of such LDPE copolymers.
[0092] More preferably, the one or more polar comonomers are selected from C1- to C6-alkyl acrylates, C1- to C6-alkyl methacrylates or vinyl acetate. Even more preferably, the LDPE copolymer used in the inner and / or outer semiconducting layers is a copolymer of ethylene and a C1- to C6-alkyl acrylate, such as methyl acrylate, ethyl acrylate, propyl acrylate or butyl acrylate or vinyl acetate.
[0093] Preference is given to using ethylene methyl acrylate (EMA) copolymers, ethylene methyl methacrylate (EMMA) copolymers, ethylene ethyl methacrylate (EEMA) copolymers, ethylene butyl methacrylate (EBMA) copolymers, ethylene ethyl acrylate (EEA) copolymers, ethylene butyl acrylate (EBA) copolymers or ethylene vinyl acetate (EVA) copolymers.
[0094] Preference is given to using ethylene methyl acrylate (EMA), ethylene butyl acrylate (EBA) or ethylene ethyl acrylate (EEA).
[0095] The LDPE copolymer of the inner and / or outer semiconducting layers preferably comprises from 0.001 to 40% by weight, more preferably from 0.05 to 40% by weight, even more preferably from 1 to 30% by weight of one or more comonomers, based on the total weight of the LDPE copolymer. The content of the polar comonomer is more preferably from 5 to 30% by weight, 5 to 25% by weight, 5 to 20% by weight, for example from 7 to 20% by weight or 10 to 20% by weight.
[0096] Preferably, the LDPE copolymer of the inner semiconducting layer and / or the outer semiconducting layer has a melt flow rate MFR2.16 / 190°C of 0.1 to 50 g / 10 min, more preferably 1.0 to 30 g / 10 min, even more preferably 2.0 to 25 g / 10 min, still more preferably 3.0 to 22.0 g / 10 min, most preferably 4.0 to 21.0 g / 10 min, for example 5.0 to 20.0 g / 10 min.
[0097] The LDPE copolymer has a viscosity of 910 to 940 kg / m 3 , preferably 915 to 940 kg / m 3 , for example 920~940kg / m 3 , has a density of
[0098] The inner and / or outer semiconducting layers may comprise at least 50% by weight, such as at least 55% by weight, of the LDPE copolymer, based on the total weight of the individual semiconducting layers. When a blend of LDPE copolymers is used, this percentage refers to the total of the LDPE copolymers present.
[0099] In some embodiments, there is at least 60% by weight of LDPE copolymer in the inner and / or outer semiconducting layer, based on the total weight of each individual semiconducting layer. The LDPE copolymer typically forms the remainder of the layer once the other components of the semiconducting layer are selected. The inner and / or outer semiconducting layer preferably comprises 90% by weight or less of LDPE copolymer.
[0100] Polymerization Process
[0101] Generally, any of the LDPE homopolymers or copolymers of the present invention described in any of the sections described above or below can be produced by any conventional polymerization process. Preferably, it is produced by radical polymerization, e.g. high pressure radical polymerization. The high pressure polymerization can be carried out in a tubular reactor or an autoclave reactor. Preferably, it is a tubular reactor. Generally, the pressure can be in the range of 1200 to 3500 bar, and the temperature can be in the range of 100°C to 350°C. Further details regarding high pressure radical polymerization are given in Encyclopedia of Polymer Science and Engineering, Vol. 6 (1986), pp 383-410 and Encyclopedia of Materials: Science and Technology, Elsevier Science Ltd.: “Polyethylene: High-pressure, R. Klimesch, D. Littmann and F.-O. Mahling pp. 7181-7184, (2001), which are incorporated herein by reference.
[0102] For example, it is well known that propylene can be used as a comonomer or as a chain transfer agent (CTA), or both, thereby contributing to the total amount of C-C double bonds, preferably the total amount of vinyl groups. For the purposes of the present invention, when a compound that can also act as a comonomer is specifically used during polymerization as a CTA to provide double bonds, said copolymerizable comonomer is not calculated into the comonomer content. For the purposes of the present invention, propylene may be used as a CTA and may contribute to the total amount of vinyl groups, but it is not calculated into the comonomer content.
[0103] Carbon Black - Semiconductor Layer
[0104] In accordance with the present invention, the inner and outer semiconducting layers further comprise carbon black.
[0105] The semiconducting properties are due to the added carbon black. The amount of carbon black is therefore such that at least a semiconducting layer is obtained. Preferably, the inner and / or outer semiconducting layer comprises 10-60% by weight, preferably 15-48% by weight, of carbon black, based on the total weight of the respective semiconducting layer. In another preferred embodiment, the amount of carbon black is 10-45% by weight, for example 20-45% by weight, preferably 25-45% by weight, more preferably 25-40% by weight, especially 30-41% by weight, based on the weight of the respective semiconducting layer.
[0106] Any carbon black that is conductive can be used. Examples of suitable carbon blacks include furnace blacks and acetylene blacks. Mixtures can also be used. When a blend of carbon blacks is used, the percentage refers to the total of the carbon blacks present.
[0107] The carbon black has a viscosity of 5 to 400 mm as determined in accordance with ASTM D3037-93. 2 / g, e.g. 10-300m 2 / g, e.g. 30-200m 2 / g. In addition, the carbon black may have one or more of the following characteristics: i) a primary particle size of at least 5 nm, defined as the number average particle size according to ASTM D3849-95a; ii) an iodine adsorption number (IAN) of at least 10 mg / g, e.g., 10 to 300 mg / g, e.g., 30 to 200 mg / g, as determined in accordance with ASTM D-1510; and / or iii) At least 30 cm when measured in accordance with ASTM D 2414 3 / 100g, for example 60~300cm 3 / 100g, for example 70~250cm 3 / 100g, for example 80~200cm 3 / 100g, for example 90~180cm 3 / 100g, DBP (dibutyl phthalate) absorption value (= oil absorption value).
[0108] Additionally, the carbon black may have one or more of the following characteristics: a) a primary particle size of at least 5 nm, defined as the number average particle size according to ASTM D3849-95a; b) an iodine value of at least 30 mg / g according to ASTM D1510; c) An oil absorption number of at least 30 ml / 100 g measured in accordance with ASTM D2414.
[0109] One group of suitable furnace blacks has an average primary particle size of 28 nm or less, defined as the number average particle size measured according to ASTM D3849-95a. Particularly suitable furnace blacks of this category may have an iodine number according to ASTM D1510 of 60 to 300 mg / g. It is further preferred that the oil absorption number (of this category) is 50 to 225 ml / 100 g, for example 50 to 200 ml / 100 g, measured according to ASTM D2414.
[0110] Another group of equally suitable furnace blacks has an average primary particle size of more than 28 nm, the average primary particle size being defined as the number average particle size according to ASTM D3849-95a. Suitable furnace blacks of this category have an iodine number according to ASTM D1510 of 30 to 200 mg / g. Furthermore, the oil absorption number (of this category) is, for example, 80 to 300 ml / 100 g, measured according to ASTM D2414.
[0111] Other suitable carbon blacks may be produced by any other process or may be further processed.
[0112] Suitable carbon blacks for semiconductive cable core layers are preferably characterized by their cleanliness: thus, suitable carbon blacks have an ash content of less than 0.2 weight percent as measured in accordance with ASTM D1506, a 325 mesh sieve residue of less than 30 ppm in accordance with ASTM D1514, and less than 1 weight percent total sulfur in accordance with ASTM D1619.
[0113] Furnace carbon black is a commonly recognized term referring to the well-known carbon black type produced in a furnace type reactor. Examples of carbon black, its preparation process and reactor can be found in EP-A-0629222 of Cabot; US Pat. No. 4,391,789, US Pat. No. 3,922,335 and US Pat. No. 3,401,020. Examples of commercial furnace carbon black grades described in ASTM D 1765-98b can be mentioned, namely N115, N220 and N550. Furnace carbon black is conventionally distinguished from acetylene carbon black, another carbon black suitable for semiconductor layers. Acetylene carbon black is produced in the acetylene black process by the reaction of acetylene with unsaturated hydrocarbons, as described, for example, in US Pat. No. 4,340,577.
[0114] In particular, the acetylene black may have an average primary particle size of more than 20 nm, for example 20-80 nm. The average primary particle size is defined as the number average particle size according to ASTM D3849-95a. Suitable acetylene blacks of this category have an iodine number of 30-300 mg / g, for example 30-150 mg / g, according to ASTM D1510. Furthermore, the oil absorption number (of this category) is for example 80-300 ml / 100 g, for example 100-280 ml / 100 g, measured according to ASTM D2414. Acetylene black is a commonly accepted term and is very well known and is supplied, for example, by Denka.
[0115] Further embodiments according to the present invention disclose a semiconducting layer in which the conductive component comprises or consists of conductive carbon black, such as carbon black having one or more, such as all, of the following characteristics: A primary particle size of at least 5 nm, defined as the number average particle size according to ASTM D3849-95a; an iodine adsorption number (IAN) of at least 10 mg / g, e.g., 10 to 300 mg / g, as determined according to ASTM D-1510; or At least 30 cm when measured according to ASTM D 2414 3 / 100g, for example 60~300cm 3 / 100g, DBP (dibutyl phthalate) absorption value (= oil absorption value).
[0116] Crosslinker - Semiconductor layer
[0117] The inner and / or outer semiconducting layers are crosslinkable or crosslinked. Several methods of crosslinking can be envisaged, but in this range, the crosslinking agent, preferably a peroxide, is preferably present in the crosslinkable inner and / or outer semiconducting layers in an amount of less than 3.0 wt%, more preferably 0.1-2.5 wt%, even more preferably 0.3-2.5 wt%, based on the total weight of the individual semiconducting layers. In some embodiments, the peroxide is present in an amount of 0.4-2.5 wt%, preferably 0.4-2.0 wt%, for example 0.4-1.4 wt%, based on the total weight of the individual semiconducting layers. When a blend of the crosslinking agents is used, this percentage refers to the total crosslinking agents present.
[0118] The preferred crosslinking agent is organic peroxide.Non-limiting examples include organic peroxide, such as di-tert-amyl peroxide, 2,5-di(tert-butylperoxy)-2,5-dimethyl-3-hexyne, 2,5-di(tert-butylperoxy)-2,5-dimethylhexane, tert-butylcumyl peroxide, di(tert-butyl)peroxide, dicumyl peroxide, butyl-4,4-bis(tert-butylperoxy)-valerate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-butylperoxybenzoate, dibenzoyl peroxide, bis(tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 1,1-di(tert-butylperoxy)cyclohexane, 1,1-di(tert-amylperoxy)cyclohexane, or any combination thereof. Preferably, the peroxide is selected from 2,5-di(tert-butylperoxy)-2,5-dimethylhexane, di(tert-butylperoxyisopropyl)benzene, dicumyl peroxide, tert-butylcumyl peroxide, or a combination thereof. Most preferably, the peroxide is bis(tert-butylperoxyisopropyl)benzene.
[0119] Antioxidants
[0120] Any layer of the undersea cable core may contain an antioxidant, which may include hindered or semi-hindered phenols, aromatic amines, aliphatic hindered amines, organic phosphates, thio compounds, polymerized 2,2,4-trimethyl-1,2-dihydroquinoline, and combinations thereof.
[0121] More preferably, the antioxidant is selected from the group of 4,4'-bis(1,1'dimethylbenzyl)diphenylamine, para-oriented styrenated diphenylamine, 4,4'-thiobis(2-tert-butyl-5-methylphenol), polymerized 2,2,4-trimethyl-1,2-dihydroquinoline, or derivatives thereof.
[0122] More preferably, the antioxidant is selected from the group consisting of, but not limited to, 4,4'-bis(1,1'dimethylbenzyl)diphenylamine, para-oriented styrenated diphenylamine, 4,4'-thiobis(2-tert-butyl-5-methylphenol), 2,2'-thiobis(6-t-butyl-4-methylphenol), distearylthiodipropionate, 2,2'-thio-diethyl-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, polymerized 2,2,4-trimethyl-1,2-dihydroquinoline, or derivatives thereof. Of course, not only one of the antioxidants listed above, but any combination thereof may be used.
[0123] The amount of one antioxidant, optionally a combination of two or more antioxidants, may be in the range of 0.005 to 2.5 wt.%, for example 0.01 to 2.5 wt.%, preferably 0.01 to 2.0 wt.%, more preferably 0.03 to 2.0 wt.%, in particular 0.03 to 1.5 wt.%, more in particular 0.05 to 1.5 wt.%, for example 0.05 to 1.3 wt.%, or 0.1 to 1.5 wt.%, for example 0.1 to 1.25 wt.%, based on the total weight of the respective semiconductor layer.
[0124] In some embodiments, the amount of one antioxidant, optionally a combination of two or more antioxidants, is from 0.03 to 2.0 wt. %, preferably from 0.04 to 1.5 wt. %, for example from 0.05 to 1.0 wt. %, more preferably from 0.05 to 0.8 wt. %, for example from 0.05 to 0.7 wt. %, or from 0.05 to 0.35 wt. %, in particular from 0.07 to 0.6 wt. %, more particularly from 0.08 to 0.5 wt. %, for example from 0.09 to 0.4 wt. %, or from 0.1 to 0.35 wt. %, based on the total weight of the insulating layer.
[0125] Other Ingredients
[0126] The inner and / or outer semiconducting layers, or the insulating layer may include further additives. Possible additives may include scorch inhibitors, crosslinking promoters, stabilizers, processing aids, flame retardant additives, acid scavengers, inorganic fillers, voltage stabilizers, or combinations thereof.
[0127] A "scorch inhibitor" is defined as a compound that reduces premature crosslinking during extrusion, i.e., the formation of scorch. In addition to the scorch inhibition properties, scorch inhibitors may simultaneously provide additional accelerating effects, i.e., enhancing crosslinking performance. The use of scorch inhibitors in the insulation layer is particularly preferred.
[0128] Useful scorch inhibitors can be selected from unsaturated dimers of aromatic alpha-methyl alkenyl monomers, aromatic alpha-methyl alkenyl monomers, substituted or unsubstituted diphenylethylene, quinone derivatives, hydroquinone derivatives such as 2,5-di-tert-butylhydroquinone, monofunctional vinyl-containing esters and ethers, or combinations thereof.More preferably, the scorch inhibitor is selected from unsaturated dimers of aromatic alpha-methyl alkenyl monomers, such as 2,4-diphenyl-4-methyl-1-pentene, substituted or unsubstituted diphenylethylene, or combinations thereof.A highly preferred option is 2,4-diphenyl-4-methyl-1-pentene.
[0129] Preferably, the amount of the scorch inhibitor is in the range of 0.005 to 1.0% by weight, more preferably in the range of 0.01 to 0.80% by weight, based on the weight of the layer in question, and even more preferably in the range of 0.03 to 0.75% by weight, 0.05 to 0.50% by weight, 0.05 to 0.70% by weight, and 0.10 to 0.50% by weight, based on the weight of the layer in question.
[0130] The crosslinking promoter may be a compound containing at least two unsaturated groups, such as aliphatic or aromatic compounds, esters, ethers, amines, or ketones, or may be a compound containing at least two unsaturated groups, such as cyanurates, isocyanurates, phosphate esters, orthoformates, aliphatic or aromatic ethers, or allyl esters of benzenetricarboxylic acids. Examples of esters, ethers, amines, and ketones are compounds selected from the general group of diacrylates, triacrylates, tetraacrylates, triallyl cyanurates, triallyl isocyanurates, 3,9-divinyl-2,4,8,10-tetra-oxaspiro[5,5]-undecane (DVS), triallyl trimellitates (TATM), or N,N,N',N',N",N"-hexaallyl-1,3,5-triazine-2,4,6-triamine (HATATA), or any combination thereof. The crosslinking promoter may be added in an amount of less than 2.0 wt. %, such as less than 1.5 wt. %, for example less than 1.0 wt. %, such as less than 0.75 wt. %, for example less than 0.5 wt. %, and the lower limit being, for example, 0.05 wt. % or more, such as 0.1 wt. % or more of such crosslinking agent, based on the total weight of the layer in question.
[0131] In a further embodiment of the present invention, the insulation layer does not contain any water tree retarders other than component (ii) discussed herein.
[0132] Preparation of the polymer composition
[0133] During the preparation of the polymer composition, the components can be blended, for example melt mixed in a compounding device. Preferably, the process does not involve the use of peroxides. Typically, the process involves heating to a temperature of at least 150°C, preferably at least 160°C, for example at least 170°C. The process generally involves heating to a temperature of 300°C or less, for example 250°C or less.
[0134] It is understood that all definitions and preferred aspects as described above apply equally to all further embodiments as described below. In one embodiment, the insulation layer composition of the present invention may contain a crosslinking agent before the composition is used for cable manufacture, whereby the polymeric components and the crosslinking agent can be blended by any conventional mixing process, such as by adding the crosslinking agent to the melt of the polymeric composition, for example in an extruder, and by adsorption of liquid peroxide, peroxide in liquid form or peroxide dissolved in a solvent, onto the polymeric solid composition, for example its pellets. The resulting insulation layer composition of components, such as, inter alia, polymeric components (i) and (ii), one or more antioxidants and crosslinking agent, is then used for the preparation process of a molded article, for example a cable core.
[0135] In another embodiment, the crosslinking agent can be added, for example, during the preparation of the crosslinkable article and forming the insulation layer composition as used in the cable core of the present invention. Then, when the crosslinking agent is added during the preparation process of the molded article, for example, the crosslinking agent as described herein is added in the form of a liquid at ambient temperature, or preheated above its melting point, or dissolved in a carrier medium, as is well known in the art.
[0136] The insulation layer composition used in the cable core of the present invention may contain one or more additional additives, or one or more additional additives may be incorporated into the polymer composition during the preparation of an article comprising the insulation layer composition. It is understood that additional additives such as antioxidants, crosslinking agents, scorch retarders, etc. may be added in the form of a masterbatch, as is well known in the art.
[0137] In a particular embodiment, the semiconducting layer used in the cable core of the present invention can be obtained by several means using several different manufacturing techniques, for example, internal mixers (e.g. Banbury or Bolling), continuous single screw (e.g. BUSS) or continuous twin screw (e.g. Farrel or Werner & Pfleiderer). The type of mixer and the selected operating conditions for the preparation of the semiconductive compound have a direct impact on the melt quality and affect the final compound properties, such as melt flow rate, volume resistivity and surface smoothness. Particularly useful is the co-kneader technology (BUSS, X-compound). In the preparation of the semiconducting layer, the conductive filler can be added to the polymer in the molten state, while fully controlling the manufacturing temperature. With this technique, a blend with a good dispersive and distributive mixing can be achieved by those skilled in the art.
[0138] It will be understood that the crosslinker is generally added to the semiconducting layer composition in a manner similar to that of the insulating layer composition, as detailed in the embodiments above.
[0139] conductor
[0140] The submarine cable core of the present invention includes a conductor, which can be made from any suitable conductive metal, such as copper or aluminum.
[0141] Submarine cables and cable cores
[0142] A submarine power cable is defined as a cable as described above for transmitting energy, comprising at least one cable core, operating at any voltage, preferably higher than 30 kV. It is understood that all definitions and preferred aspects as set out above apply equally to all further embodiments as described below.
[0143] The voltage applied to the submarine power cable can be alternating current (AC), direct current (DC) or transient (impulse). Moreover, the submarine cable according to the invention is very advantageously an AC submarine power cable, for example a submarine cable operating at a voltage (RMS voltage, voltage between any two conductors in a three-phase cable) between 1 and 525 kV, between 6 and 525 kV, between 36 and 275 kV, for example between 66 and 275 kV, between 36 and 220 kV, for example between 66 and 220 kV, between 36 and 150 kV, for example between 66 and 150 kV, and above 66 kV. In some embodiments, the submarine cable is a submarine AC power cable operating at a voltage of 33 kV or more, preferably 36 kV or more, more preferably 66 kV or more. In some embodiments, the submarine cable is an AC power cable operating at a voltage lower than 550 kV, preferably lower than 525 kV, preferably lower than 400 kV, more preferably lower than 380 kV, in particular lower than 275 kV, lower than 220 kV, or lower than 150 kV.
[0144] As is well known, the submarine cable may optionally comprise further layers, such as layers surrounding the outer semiconducting layer, e.g. a jacket layer. The presence of a moisture-tight layer preventing the ingress of water is preferably avoided, i.e. the submarine cable is a wet design cable.
[0145] A submarine cable core for use in a submarine cable comprising: (a) providing and mixing, e.g., melt mixing in an extruder, a crosslinkable first semiconducting layer composition for the inner semiconducting layer; providing and mixing, e.g., melt mixing in an extruder, a crosslinkable insulation layer composition for said insulation layer; providing and mixing, e.g., melt mixing in an extruder, a second semiconducting layer composition for the outer semiconducting layer; (b) applying it onto the conductor, for example by coextrusion; melt mixing the first semiconducting layer composition obtained from step (a) to form an inner semiconducting layer; Melting and mixing the insulating layer composition obtained from step (a) to form an insulating layer; and melt mixing the second semiconducting layer composition resulting from step (a) to form an outer semiconducting layer; and (c) optionally crosslinking one or more of the insulating layer, the inner semiconducting layer, and the outer semiconducting layer of the resulting submarine cable core under crosslinking conditions. It can be produced by a method including the steps of:
[0146] It is understood that the individual layer compositions of the present invention may contain the crosslinking agent before the composition is used to manufacture a cable, or the crosslinking agent may be added at a stage, for example, during the preparation of the crosslinkable article.
[0147] When peroxides are used in the manufacture of the layers of the submarine cable core, it is preferred that such layers are crosslinked, and therefore the submarine cable core is crosslinkable.
[0148] The first semiconducting composition for the inner semiconducting layer, the crosslinkable insulating composition for the insulating layer, and the second semiconducting composition for the outer semiconducting layer comprise the necessary components to form the respective inner semiconducting layer, insulating layer and outer semiconducting layer of the submarine cable core.
[0149] Preferably, all layers are crosslinked.The present invention therefore further provides a crosslinked submarine cable core obtained by crosslinking a submarine cable core as defined herein.
[0150] The crosslinking procedure may be carried out at elevated temperatures, for example above 150°C, for example from 160 to 350°C.
[0151] Melt mixing means mixing the resulting mixture at a temperature above the melting point of at least the major polymer component(s), and is typically carried out at a temperature at least 10-15° C. above the melting or softening point of the polymer component(s).
[0152] The term "coextrusion" as used herein means that one or more layers are formed in whole or in part simultaneously using one or more extrusion heads. For example, triple extrusion can be used to form three layers.
[0153] In a further embodiment of the present invention, the crosslinked submarine cable core of the present invention has a crosslinking strength of 4.5×10 -4 Less than or equal to 4×10 -4 For example, 3.5×10 -4 Less than or equal to 3×10 -4 For example, 2.5×10 -4 tan δ measured on a 10 kV cable at 90°C and 5 kV / mm, and / or 12 x 10 -4 Less than or equal to 10x10 -4 For example, 8×10 -4 Less than or equal to 7.5×10 -4 For example, 6.5×10 -4 , measured on a 10 kV cable at 90° C. and 10 kV / mm.
[0154] In a still further embodiment of the present invention, the crosslinked submarine cable of the present invention has an AC electrical breakdown strength value (or Weibull Eb), measured on a 20 kV cable (nominal insulation thickness of 5.5 mm), after 1 year of wet aging in salt water, as described in the Determination Methods section below, of at least 40 kV / mm, such as at least 41 kV / mm, 42 kV / mm, 43 kV / mm or 44 kV / mm, preferably at least 45 kV / mm, more preferably at least 46 kV / mm, even more preferably at least 47 kV / mm, and most preferably at least 48 kV / mm. The upper level of the AC electrical breakdown strength value (or Weibull Eb) is understood to be, but is not limited to, having an AC electrical breakdown strength value (or Weibull Eb) of, but is not limited to, preferably less than 60 kV / mm or less than 55 kV / mm, measured on a 20 kV cable (nominal insulation thickness of 5.5 mm) after one year of wet aging in salt water, as described in the Determination Method section below.
[0155] Further, the first semiconductor composition and the second semiconductor composition can, for example, be the same.
[0156] The thickness of the insulation layer of the submarine power cable, e.g., submarine AC cable, is typically 2 mm or more, such as at least 2.5 mm, at least 3 mm, such as at least 3.5-50 mm, such as 4-50 mm, preferably at least 4.5-35 mm, such as 5-30 mm, when measured from a cross-section of the insulation layer of the submarine cable.
[0157] The thickness of the inner and / or outer semiconductor layer of the submarine power cable may typically be 0.4 mm or more, such as 0.5 mm or more, for example in the range 0.7 mm to 5.0 mm, when measured from a cross-section of the layer.
[0158] Viewed from another aspect, the present invention provides a submarine power cable, more preferably a submarine AC power cable, comprising at least one cable core comprising a conductor surrounded, in order, by at least an inner semiconducting layer, an insulating layer and an outer semiconducting layer, wherein the inner semiconductor layer and / or the outer semiconductor layer independently comprise, based on the total weight of the individual semiconductor layers: at least 50% by weight of an LDPE copolymer having a polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, or vinyl acetate; 25 to 48 weight percent carbon black; and 0.1 to 2.5% by weight peroxide and Here, the insulating layer comprises, based on the total weight of the insulating layer, (i) a low density polyethylene homopolymer or copolymer having at least one polyunsaturated comonomer and, optionally, one or more further comonomers; (ii) a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, or vinyl acetates; and (iii) 0.1 to 2.5% by weight of peroxide Including, wherein the amount of polar monomer units in the insulating layer is 1 to 150 micromoles per gram based on the total amount of polymer components in the insulating layer; The above submarine power cable is provided.
[0159] How to use
[0160] The submarine cable of the present invention is particularly adapted for use in a salt water environment, especially in a salt water environment at high pressure. The cable may therefore be buried in the sea or may be located under the sea or on the seabed. Submarine cables buried on land but close to the shore may also be exposed underground to salt water environments. Submarine cables used in tidal estuaries are also exposed to salt water. There are also salt water lakes and salt water seas, for example, where the cable of the present invention has utility in or under such bodies of water. The cable of the present invention is suitable for use in any salt water environment. It is further understood that all definitions and preferred aspects as set out above apply equally to all further embodiments as described below.
[0161] Viewed from another aspect, the present invention therefore provides a submarine cable comprising at least one, preferably at least two, more preferably at least three submarine cable cores as hereinbefore defined.
[0162] In a preferred embodiment according to the present invention, the submarine cable is a submarine AC cable, as previously defined herein, comprising at least three submarine cable cores.
[0163] In a more preferred embodiment according to the present invention, the submarine cable is a submarine high voltage (HV) AC cable as defined hereinbefore comprising at least three submarine cable cores, said submarine high voltage (HV) AC cable operating at a voltage of at least 30 kV.
[0164] In one embodiment, the present invention relates to a method comprising burying in the ocean a submarine cable as defined hereinbefore.
[0165] In one embodiment, the present invention relates to a method comprising laying a submarine cable as defined herein on the ocean floor. Such a submarine cable may therefore be unwound from a spool. Such a process may involve a submarine cable laying vessel.
[0166] In one embodiment, the cable of the present invention may be used to connect an offshore power generation system to shore, and therefore the submarine cable lies on the ocean floor.
[0167] Therefore, from another point of view, the present invention provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: (a) Offshore generators, e.g. wind turbines; (b) a cable as described herein connecting the offshore generator through the sea or seabed to a substation located offshore and / or onshore; The present invention provides a power generation system comprising:
[0168] Offshore wind turbines are typically mounted on an offshore platform and connected to an offshore substation mounted on another platform and / or to an onshore substation by submarine cables. These submarine cables, and thus the submarine cable of the present invention, which functions exceptionally in the presence of seawater, are ideally suited for this application.
[0169] Thus, in general, the submarine cable of the present invention may connect offshore equipment with land equipment or other offshore equipment. Thus, the submarine cable of the present invention may connect these equipment via the sea or under the sea.
[0170] In one embodiment, the submarine cable of the present invention may be used to distribute power generated in an offshore power generation system and connect the system via the sea or under the sea to substations or collection systems located offshore and / or on land.
[0171] In one embodiment, the present invention provides a method of operating a submarine cable, comprising: Three submarine cable cores as defined herein above; Armour surrounding the three submarine cable cores; providing a submarine cable comprising: Transmitting AC power through the three submarine cables The present invention relates to the above-mentioned operation method including:
[0172] According to one embodiment, transmitting the AC power includes supplying AC power generated by the wind power generation system to a corresponding onshore substation. According to an alternative embodiment, transmitting the AC power includes supplying the AC power from the onshore substation to the wind farm power generation system.
[0173] The submarine cable of the invention is particularly suitable for power generation plants, such as offshore wind farms, tidal systems or wave systems.
[0174] The invention will now be described with reference to the following non-limiting examples.
[0175] How to decide
[0176] Unless otherwise stated in the detailed description or experimental section, the following methods were used for characterization.
[0177] wt%: weight%
[0178] Melt Flow Rate
[0179] The melt flow rate (MFR) is determined according to ISO 1133 and is given in g / 10 min. The MFR is a measure of the flowability and therefore processability of a polymer. The higher the melt flow rate, the lower the viscosity of the polymer. The MFR is determined for polyethylene at 190° C. and is measured under different loads, e.g. 2.16 kg (MFR2) or 21.6 kg (MFR 21 ), can be determined.
[0180] density
[0181] Density was measured according to ISO 1183-1 / Method A. Sample preparation was performed by compression molding according to ISO 17855-2:2016.
[0182] Comonomer Content
[0183] a) Quantification of alpha-olefin content in low density polyethylene by NMR spectroscopy
[0184] The comonomer content was quantitatively determined after basicity assignment. 13 The C content was determined by C nuclear magnetic resonance (NMR) spectroscopy (J. Randall JMS-Rev. Macromol. Chem. Phys., C29(2&3), 201-317 (1989)). The experimental parameters were adjusted to ensure the measurement of a quantitative spectrum for this particular task.
[0185] In particular, solution-state NMR spectroscopy was used using a Bruker AvanceIII 400 spectrometer. Homogeneous samples were prepared by dissolving approximately 0.200 g of polymer in 2.5 ml of deuterated tetrachloroethene in a 10 mm sample tube at 140° C. using a heat block and rotating tube oven. Proton decoupled with (power controlled) NOE was used. 13C single-pulse NMR spectra were recorded using the following acquisition parameters: flip-angle 90 degrees, 4 dummy scans, 4096 transients, 1.6 s observation time, 20 kHz spectral width, temperature 125 °C, bilevel WALTZ proton decoupling scheme, and 3.0 s delay time. The resulting FIDs were processed using the following processing parameters: apodisation using a Gaussian window function with zero-filling to 32k data points; automatic zero- and first-order phase correction and automatic baseline correction using a fifth-order polynomial restricted to the region of interest.
[0186] Quantities were calculated using simple correction ratios of the signal integrals of representative sites based on methods well known in the art.
[0187] b) Determination of the comonomer content of polar comonomers in low density polyethylene
[0188] Comonomer content (wt %) was determined in a known manner based on Fourier transform infrared spectroscopy (FTIR) determinations calibrated with quantitative nuclear magnetic resonance (NMR) spectroscopy.
[0189] The films were pressed at 150°C, approximately 5 tons, for 1-2 minutes using a Specac film press and then cooled uncontrolled using cold water. The exact thickness of the resulting film samples was measured.
[0190] After analysis with FTIR, the baseline of the absorbance mode was drawn with respect to the peak to be analyzed. The absorbance peak of the comonomer was normalized by that of polyethylene. The FTIR peak height ratio was correlated with the polar comonomer content by reference materials determined by NMR. The calibration procedure for NMR spectroscopy was carried out in a conventional manner that is well documented in the literature.
[0191] Quantifying polar comonomer content in polymers by NMR spectroscopy
[0192] The polar comonomer content was measured by quantitative nuclear magnetic resonance (NMR) spectroscopy after base assignment (e.g., “NMR Spectra of Polymers and Polymer Additives”, AJ Brandolini and DDHills, 2000, Marcel Dekker, Inc. New York). Experimental parameters were adjusted to ensure quantitative spectral measurements for this particular problem (e.g., “200 and More NMR Experiments: A Practical Course”, S. Berger and S. Braun, 2004, Wiley-VCH, Weinheim). The amount was calculated using a simple correction ratio of the signal integrals of representative sites in a manner known in the art.
[0193] In the following, the determination of the polar comonomer content of ethylene ethyl acrylate, ethylene butyl acrylate and ethylene methyl acrylate is exemplified.
[0194] Weight percent can be converted to mole percent by calculation, which is well documented in the literature.
[0195] (1) Ethylene copolymer containing butyl acrylate
[0196] Polymer film samples were prepared for FTIR measurements: 0.5-0.7 mm thick films were used for ethylene butyl acrylate content >6 wt% butyl acrylate content, and 0.05-0.12 mm thick films were used for ethylene butyl acrylate content <6 wt% butyl acrylate content.
[0197] After FT-IR analysis, 3450cm -1 The maximum absorbance of the peak for more than 6 wt.% butyl acrylate at 3510 cm -1 The baseline absorbance value at 100 nm was subtracted (A ブチルアクリレート -A 3510 ) Next, 2020cm -1 The maximum absorbance peak for the polyethylene peak at 2120 cm -1 The baseline absorbance value at 100 nm was subtracted (A 2020 -A 2120 ). Next, (A ブチルアクリレート -A 3510 ) and (A 2020 -A 2120 ) was calculated in a conventional manner that is well documented in the literature.
[0198] 1165cm -1 The maximum absorbance of the peak for less than 6 wt.% butyl acrylate comonomer at 1865 cm -1 The baseline absorbance value at 100 nm was subtracted (A ブチルアクリレート -A 1865 ) Next, 2660cm -1 The maximum absorbance peak for the polyethylene peak at 1865 cm -1 The absorbance value for the baseline at 100 nm was subtracted. Then, (A 2660 -A 1865 ). (A ブチルアクリレート -A 1865 ) and (A 2660 -A 1865 ) was calculated.
[0199] (2) Ethylene copolymer containing ethyl acrylate
[0200] Polymer film samples were prepared for FTIR measurements: 0.5 mm thickness was used for ethylene ethyl acrylate.
[0201] After FT-IR analysis, approximately 3205-3295 cm -1 A linear baseline correction was applied at 3450 cm -1 The maximum absorbance (A) for the peak for ethyl acrylate at エチルアクリレート ) was determined. Next, approximately 1975~2120cm -1 A linear baseline correction was applied at 2020 cm -1 The maximum absorbance peak for the polyethylene peak was measured (A 2020 ). Next, (A エチルアクリレート ) and (A 2020 ) was calculated in a conventional manner that is well documented in the literature.
[0202] (3) Ethylene copolymers containing methyl acrylate
[0203] Polymer film samples were prepared for FTIR measurements: 0.1 mm thickness was used for ethylene methyl acrylate content >8 wt.% methyl acrylate content and 0.05 mm thickness was used for ethylene methyl acrylate content <8 wt.% methyl acrylate content.
[0204] After analysis, 3455cm -1 The maximum absorbance of the peak for more than 8 wt.% methyl acrylate at 3510 cm -1 The absorbance value for the baseline at 100 nm was subtracted (A メチルアクリレート -A 3510 ) Next, 2675cm -1 The maximum absorbance peak for the polyethylene peak is at 2450 cm -1 The absorbance value for the baseline was subtracted (A 2675 -A 2450 ). Next, (A メチルアクリレート -A 3510 ) and (A 2675-A 2450 ) was calculated in a conventional manner that is well documented in the literature.
[0205] 1164cm -1 The maximum absorbance of the peak for less than 8 wt.% methyl acrylate comonomer at 1850 cm -1 The baseline absorbance value at 100 nm was subtracted (A メチルアクリレート -A 1850 ) Next, 2665cm -1 The maximum absorbance peak for the polyethylene peak at 1850 cm -1 The absorbance value for the baseline at 100 nm was subtracted (A 2665 -A 1850 ). Next, (A メチルアクリレート -A 1850 ) and (A 2665 -A 1850 ) was calculated.
[0206] ASTM D3124-98 and ASTM D6248-98 for determining the amount of double bonds in polymers, i.e., polyethylene
[0207] The methods ASTM D3124-98 and ASTM D6248-98 are applied for the determination of double bonds in LDPE component (i), which in the description of the methods is referred to as "polymer".
[0208] The ASTM D3124-98 method and the ASTM D6248-98 method on the other hand contain a procedure for the determination of the amount of double bonds / 1000 C atoms based on ASTM D3124-98. In the ASTM D3124-98 method, a detailed description for the determination of vinylidene groups / 1000 C atoms is given based on 2,3-dimethyl-1,3-butadiene. In the ASTM D6248-98 method, a detailed description for the measurement of vinyl groups and trans-vinylene groups / 1000 C atoms is given based on 1-octene and trans-3-hexene, respectively. The sample preparation procedures described therein were applied here for the determination of vinyl groups / 1000 C atoms, vinylidene groups / 1000 C atoms and trans-vinylene groups / 1000 C atoms in the present invention. Although ASTM D6248-98 suggests the possibility of including the bromination procedure of ASTM D3124-98, the samples related to the present invention were not brominated. For the determination of the extinction coefficients for these three types of double bonds, the following three compounds were used: 1-decene for vinyl, 2-methyl-1-heptene for vinylidene, and trans-4-decene for trans-vinylene, and the procedures described in ASTM D3124-98 and ASTM D6248-98 were followed with the exceptions mentioned above.
[0209] The total amount of vinyl, vinylidene and trans-vinylene double bonds of the "Polymers" was analyzed by IR spectroscopy and given as the amount of vinyl, vinylidene and trans-vinylene double bonds per 1000 carbon atoms.
[0210] The polymer to be analyzed was compressed into a thin film with a thickness of 0.5-1.0 mm. The actual thickness was measured. FT-IR analysis was performed on a Perkin Elmer Spectrum One. Two scans were performed on a 4 cm -1 The data was recorded with a resolution of .
[0211] 1) Polymer compositions comprising polyethylene homopolymers and copolymers, or polyethylene homopolymers and copolymers, except for polyethylene copolymers having more than 0.4% by weight of a polar comonomer.
[0212] For polyethylene, three types of C=C-containing functional groups were quantified by their characteristic absorptions and analyzed using different model compounds, i.e. Vinyl (R-CH=CH2), 910cm based on 1-decene [dec-1-ene] -1 Through E = 13.13 L mol -1 mm -1 Give Vinylidene (RR'C=CH2), 888cm based on 2-methylhept-1-ene -1 Through E = 18.24 L mol -1 mm -1 Give Trans-vinylene (R-CH=CH-R'), 965 cm based on trans-4-decene [(E)-dec-4-ene] -1 Through E = 15.14 L mol -1 mm -1 Give , resulting in individual extinction coefficients.
[0213] For polyethylene homopolymers or polyethylene copolymers with less than 0.4% by weight of a polar comonomer, a linear baseline correction is performed between approximately 980 and 840 cm. -1 was applied.
[0214] 2) A polymer composition comprising a polyethylene copolymer or a polyethylene copolymer having more than 0.4% by weight of a polar comonomer.
[0215] For polyethylene copolymers with more than 0.4 wt. % polar comonomer, the two types of C=C-containing functional groups were quantified by their characteristic absorptions and analyzed using different model compounds, i.e. Vinyl (R-CH=CH2), 910cm based on 1-decene [dec-1-ene] -1 Through E = 13.13 L mol -1 mm -1 Give Vinylidene (RR'C=CH2), 888cm based on 2-methylhept-1-ene -1Through E = 18.24 L mol -1 mm -1 Give , resulting in individual extinction coefficients.
[0216] EBA: For the ethylene butyl acrylate (EBA) system, the linear baseline correction is approximately 920-870 cm -1 was applied.
[0217] EEA: For the ethylene ethyl acrylate (EEA) system, the linear baseline correction is approximately 920-825 cm -1 was applied.
[0218] EMA: For the ethylene methyl acrylate (EMA) system, the linear baseline correction is approximately 930-870 cm -1 was applied.
[0219] However, the ASTM D3124-98 and ASTM D6248-98 methods also include procedures for determining the molar extinction coefficient: 0.18 mol L in carbon disulfide (CS2). -1 Solutions were used at least three times and the average molar extinction coefficient was used.
[0220] The amount of vinyl groups derived from polyunsaturated comonomers per 1000 carbon atoms was determined and calculated as follows: The polymer to be analyzed and the reference polymer were produced in the same reactor using essentially the same conditions, i.e., similar peak temperature, pressure and production rate, with the only difference being that polyunsaturated comonomer was added to the polymer to be analyzed and not to the reference polymer. The total amount of vinyl groups in each polymer was determined by FT-IR measurement as described herein. The base level of vinyl groups, i.e., vinyl groups formed by the process and vinyl groups formed from chain transfer agents that produce vinyl groups (if any), was then assumed to be the same in the reference polymer and the analyzed polymer, with the only exception that in the analyzed polymer, polyunsaturated comonomer was also added to the reactor. This base level was then subtracted from the measured amount of vinyl groups in the analyzed polymer, resulting in the amount of vinyl groups attributable to polyunsaturated comonomer / 1000 C atoms.
[0221] Tan δ measurement of 10kV cable
[0222] Cable Core Manufacturing
[0223] A 10 kV cable core with the following dimensions (described below) is extrusion vulcanized on a pilot CCV cable line with triple head using a line speed of 5.76 m / min and the following heating zone temperatures (vulcanization tube temperatures 490 / 415 / 395 / 375°C), and then the cable core is water quenched. The semiconducting layer used in the two 10 kV cable cores (insulation thickness approximately 3.5 mm) comprises the same semiconducting material in both the inventive and comparative examples.
[0224] The inner and outer semiconducting layers comprise LE0595 (containing carbon black and peroxide) supplied by Borealis. The cable core dimensions are as follows: 50mm 2 Aluminum conductor Inner semiconductor layer: 1.0±0.1mm thick Insulation layer: 3.5~3.6mm thick Outer semiconductor layer: 1.0±0.1mm thick
[0225] conditioning:
[0226] The cable cores were heat treated at 70° C. for 72 hours in a ventilated oven before measuring tan δ. After conditioning, the cable cores were stored at room temperature.
[0227] Cable core sample preparation and tan δ measurement
[0228] The working length of the cable core is more than 10m, and is usually 10-15m. The ends of the cable core are terminated with water terminations through which deionized water circulates. Guard rings are attached to both ends of the insulation, about 1cm from the insulating screen at the water terminations. The guard rings are connected to earth, and the last part of the insulating screen at the water terminations is further covered with insulating tape to eliminate measurement errors from the terminations.
[0229] Tangent delta measurements were performed with the cable core wound in an oven. For tests above room temperature, the active part of the cable core between the oven and the water termination (approximately 50 cm on each end) is surrounded by a metal pipe with circulating air from the oven. In this way, the entire live part of the cable core is exposed to the same temperature up to the water termination.
[0230] The active area is covered with aluminum foil.
[0231] To reach a stable temperature, the cable core is heated in the oven for at least 1.5 hours to reach an isothermal state. In this way, the cable core is heated by the oven and not by the conductor heating.
[0232] Tan δ measurements are made using a measuring bridge Tettex 2840. Measurements at each voltage level are taken when the bridge shows a stable value, usually within 1 minute. In the example, the applied voltage levels were adjusted to reach the following conductor stresses (5 kV / mm, 10 kV / mm and 15 kV / mm) to determine tan δ at a cable core temperature of 90°C.
[0233] Wet aging test in saltwater
[0234] Cable Core Manufacturing:
[0235] A 20 kV cable core with the following dimensions (described below) is extrusion vulcanized on a pilot CCV cable line with triple head using a line speed of 2.79 m / min and the following heating zone temperatures (vulcanization tube temperatures 460 / 400 / 385 / 375° C.), and then the cable core is water quenched. The semiconducting layer used in the two 20 kV cables (insulation thickness of approximately 5.5 mm) comprises the same semiconducting material in both the inventive and comparative examples.
[0236] The inner and outer semiconducting layers comprise LE0595 (containing carbon black and peroxide) supplied by Borealis. The cable core dimensions are as follows: 150mm 2 Aluminum conductor Inner semiconductor layer: 1.0±0.1mm thick Insulation layer: 5.5~5.6mm thick Outer semiconductor layer: 1.0±0.1mm thick
[0237] The wet ageing characteristics of the cable core in salt water are evaluated using the regime A procedure described in Cigre's Technical Brochure 722, "Recommendations for additional testing for submarine cables from 6kV (Um=7.2kV) up to 60kV (Um=72.5kV)", published in April 2018.
[0238] Preconditioning: The cable core is immersed in a water bath for 500 hours at a temperature of 55° C. The sodium chloride content of the water is 3.5% by weight.
[0239] Aging: The cable core is electrically aged in a water bath. The water temperature is 40° C. and the applied voltage is 50 kV at 50 Hz, equivalent to a conductor stress of 12 kV / mm. The sodium chloride content of the water is 3.5% by weight.
[0240] AC breakdown test:
[0241] AC breakdown tests after 1 year aging were performed according to Cigre technical brochure 722 item 3.6.4.1 and HD 605 5.4.15.3.4 (b). The cable cores were cut into 6 test samples of 10m effective length (in addition to the ends). The samples were tested to breakdown within 72 hours after removal from the aging tank with a 50Hz AC step test according to the following procedure: - Start at 36 kV for 5 min, -The voltage is increased by 12 kV every 5 minutes until breakdown occurs.
[0242] Calculation of AC breakdown strength values and Weibull parameters for a data set of breakdown values follows the least squares regression method described in IEC 62539 (2007).
[0243] Experimental section
[0244] In these examples, the following materials were used: EEA 1 is a high pressure produced LDPE copolymer of ethylene and 15 wt% ethyl acrylate comonomer (i.e., a polar comonomer). The MFR2 is approximately 7 g / 10 min.
[0245] LDPE1 is a high pressure produced LDPE copolymer of ethylene and 1,7-octadiene comonomer (i.e., a polyunsaturated comonomer) having a vinyl content of approximately 0.50-0.55 vinyl / 1000 C and an MFR2 of approximately 2 g / 10 min.
[0246] DCP: Dicumyl peroxide
[0247] Preparation of the Insulation Layer Composition
[0248] Insulation layer compositions used for the inventive and comparative cable core formulations were prepared and compared (see Table 1 below). The antioxidants described herein were added in the amounts described herein to the polymeric components of the inventive and comparative insulation layer compositions by compounding and melt mixing to form intermediate compositions that were then pelletized. The crosslinking agent was added to these intermediate compositions by dispensing the crosslinking agent (which is in liquid form) onto the pellets of the intermediate composition. The wet pellets were stored until the pellets were dry. The amount of crosslinking agent used to crosslink the different compositions is shown in the description of the inventive and comparative insulation layer compositions in Table 1 below. A scorch inhibitor with CAS number 6362-80-7 was added to the compositions in a similar manner as the crosslinking agent.
[0249] [Table 1]
[0250] The dielectric loss was determined by tan δ measurements at different conductor stresses for the inventive example as well as Comparative Example 1. Table 2 below summarizes the measured tan δ values.
[0251] It can be clearly seen that the dielectric loss of the inventive Example 1 is much lower than that of the conventional polymer WTR solution, Comparative Example 1.
[0252] [Table 2]
[0253] The AC electrical breakdown strength is measured after one year of wet aging in salt water as described above for a 20 kV cable including Example 1 of the present invention. In the one year test results after AC breakdown test, the inventors believe that there is a clear advantage in using the insulating composition according to the present invention in wet aging in salt water environment.
[0254] For the cable insulated with the polymer composition of Example 1 of the present invention, the Weibull Eb (63.2%) value after one year of wet aging was 48.8 kV / mm. The dielectric breakdown value meets the criteria set forth in CIGRE TB722 assuming a design conductor stress of 8 kV / mm. These results confirm the advantages of the composition according to the present invention and show that it is particularly suitable for use in salt water environments.
[0255] Table 3 below summarizes the measured Eb values and the test conditions.
[0256] [Table 3]
Claims
1. A submarine cable core comprising a conductor surrounded by at least an inner semiconducting layer, an insulating layer, and an outer semiconducting layer, in that order, The insulating layer is (i) a low density polyethylene homopolymer or copolymer comprising at least one polyunsaturated comonomer and, optionally, one or more further comonomers; and (ii) a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, and vinyl acetates; Including, wherein the amount of polar monomer units in the insulating layer is 1 to 150 micromoles per gram based on the total amount of polymer in the insulating layer; The submarine cable core.
2. At least one of the inner semiconductor layer and the outer semiconductor layer independently comprises: (a) a low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, and vinyl acetate; and (b) Carbon black 2. The submarine cable core of claim 1, comprising:
3. 3. A submarine cable core according to claim 1 or 2, wherein the inner semiconductor layer has the same chemical composition as the outer semiconductor layer.
4. A submarine cable core according to claim 2 or 3, wherein the inner and / or outer semiconducting layer comprises an ethylene alkyl acrylate copolymer or an ethylene vinyl acetate copolymer, preferably an ethylene alkyl acrylate copolymer.
5. A submarine cable core according to any one of claims 1 to 4, wherein component (ii) of the insulating layer is an ethylene alkyl acrylate copolymer.
6. A submarine cable core according to claim 5, wherein said ethylene alkyl acrylate copolymer is ethylene methyl acrylate, ethylene ethyl acrylate or ethylene butyl acrylate, preferably ethylene ethyl acrylate.
7. A submarine cable core according to any one of claims 1 to 6, wherein the polyunsaturated comonomer of the low density polyethylene copolymer of component (i) is a linear carbon chain having at least 8 carbon atoms and having at least 4 carbon atoms between non-conjugated double bonds, at least one of which is terminal.
8. The polyunsaturated comonomer of the low density polyethylene copolymer of component (i) is 8 -~C 14 - a non-conjugated diene, preferably selected from 1,7-octadiene, 1,9-decadiene, 1,11-dodecadiene, 1,13-tetradecadiene or a combination thereof, more preferably selected from 1,7-octadiene, 1,9-decadiene, 1,11-dodecadiene or 1,13-tetradecadiene.
9. A submarine cable core according to any one of claims 1 to 8, wherein at least one of the insulating layer, the inner semiconducting layer and the outer semiconducting layer comprises a cross-linking agent, preferably a peroxide.
10. A submarine cable core according to any one of claims 1 to 9, wherein the conductor comprises aluminum.
11. A submarine cable core according to any one of claims 1 to 10, comprising a conductor surrounded by at least an inner semiconductor layer, an insulating layer and an outer semiconductor layer in this order; wherein the inner semiconductor layer and / or the outer semiconductor layer independently comprise, based on the total weight of each individual semiconductor layer: (a) at least 49.5% by weight of a low density polyethylene copolymer comprising a polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, and vinyl acetates; (b) 25 to 48 weight percent carbon black; and (c) 0.1 to 2.5% by weight of peroxide Including, wherein the insulating layer has a composition based on a total weight of the insulating layer. (i) at least 88.0% by weight of a low density polyethylene homopolymer or low density polyethylene copolymer having at least one polyunsaturated comonomer and, optionally, one or more additional comonomers; and (ii) 0.5 to 9.50 wt. % of a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, and vinyl acetates; (iii) 0.1 to 2.5 wt. % of a peroxide; Including, wherein the amount of polar monomer units in the insulating layer is 1 to 150 micromoles per gram based on the total amount of polymer in the insulating layer. The submarine cable core.
12. A crosslinked submarine cable core obtainable by crosslinking the cable core according to any one of claims 1 to 11.
13. (i) When measured on a 10 kV cable as described in the "Determination method", the dielectric loss, measured by the tan δ value at 90 °C and 5 kV / mm, is 4.5 × 10 -4 Less than or equal to 4 x 10 -4 For example, 3.5×10 -4 Less than or equal to 3×10 -4 For example, 2.5×10 -4 and / or the dielectric loss, as measured by tan δ at 90° C. and 10 kV / mm, is less than or equal to 12×10 -4 Less than or equal to 10x10 -4 For example, 8×10 -4 Less than or equal to 7.5×10 -4 For example, 6.5×10 -4 and / or (ii) Having an AC breakdown strength value of at least 40 kV / mm, preferably at least 45 kV / mm, after one year, when measured on a 20 kV cable as described in the "Determination Method"; 13. A crosslinked submarine cable core according to claim 12.
14. Use of a submarine cable core according to any one of claims 1 to 11 or a crosslinked submarine cable core according to claim 12 or 13, for example for transmitting electricity in a submarine cable in a saltwater environment, for example under the sea or on the sea bed.
15. A submarine cable comprising at least one, preferably at least two, more preferably at least three submarine cable cores according to any one of claims 1 to 14.
16. 16. A submarine cable according to claim 15, which is a submarine AC cable system, preferably a submarine high voltage (HV) AC cable system.
17. 1. A power generation system comprising: (a) Offshore generators, such as wind turbines; (b) a submarine cable as claimed in claim 15 or 16, connecting the offshore generator via the sea or the seabed to a substation located offshore and / or on land. The power generation system.
18. 1. A method for minimizing water tree degradation and dielectric loss measured by tan δ of a submarine cable core used in a submarine cable in a salt water environment, e.g., under the sea or on the seabed, comprising using a low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates or vinyl acetate in an insulating layer of said submarine cable, wherein the amount of polar monomer units in said insulating layer is 1 to 150 micromoles per gram based on the total amount of polymer components in said insulating layer; the submarine cable core comprises a conductor surrounded by at least an inner semiconducting layer, an insulating layer, and an outer semiconducting layer, in that order; Here, the insulating layer is (i) a low density polyethylene homopolymer or copolymer comprising at least one polyunsaturated comonomer and, optionally, one or more further comonomers; and (ii) a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, and vinyl acetates; Including, wherein the amount of polar monomer units in the insulating layer is 1 to 150 micromoles per gram based on the total amount of polymer components in the insulating layer; The method.
Citation Information
Patent Citations
Polymer composition having improved wet ageing properties
EP1731566A1
The cable insulation composition - table
JP1986502085A
Electrical insulating resin composition
JP1996319381A
Polyethylene-based resin composition for insulator and high-frequency coaxial cable using the same
JP2012211315A
Underwater cable, underwater cable laying structure and laying method of underwater cable
JP2015138579A